2011
DOI: 10.1007/s11839-011-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

Supporting oncology health professionals: a review

Abstract: Background: Caring for patients with cancer can be both personally rewarding and stressful. Confrontation with suffering, working with people facing complex lifethreatening illness, demanding treatment regimens and frequent death of patients are challenging for many clinicians. Responding to the emotional needs of patients and families is often perceived as among the most stressful. These emotional sources of stress can be compounded by organisational factors and work demands. The resulting emotional impact ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 56 publications
(61 reference statements)
2
30
0
2
Order By: Relevance
“…Until recently supervision was not widely used outside of psychology and psychiatry (Turner et al, 2011); however, the present findings contribute to emerging research suggesting links between supervision and burnout. One study found that health professionals, including nurses, who received supervision for a period of six months reported higher levels of personal accomplishment (Hyrkas et al, 2006).…”
Section: Training and Supervision In Psychosocial Carementioning
confidence: 45%
“…Until recently supervision was not widely used outside of psychology and psychiatry (Turner et al, 2011); however, the present findings contribute to emerging research suggesting links between supervision and burnout. One study found that health professionals, including nurses, who received supervision for a period of six months reported higher levels of personal accomplishment (Hyrkas et al, 2006).…”
Section: Training and Supervision In Psychosocial Carementioning
confidence: 45%
“…Due to the small numbers of participants in this study, it was difficult to conclusively measure the effectiveness of these coping strategies. However, ignoring the emotional responses to the suffering of patients and not acknowledging this potentially preventable source of an ongoing stressor within the workforce are more likely to contribute to burnout [22].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in terms of potential counselling strategies for cancer care workers, it is salutary to reflect on the comment made by Turner and colleagues [22] that, despite cancer care workers having better access to healthcare, many are less likely to actively seek and receive appropriate care, perhaps because of the stigma associated with acknowledging emotional problems. Improving awareness of the availability and success of counselling interventions for stress management in the workplace may therefore represent the first task of counsellors who offer their services to cancer care staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations